Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1063/1.2216703
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular processes in CH2OH below the dissociation barrier: O–H stretch overtone excitation and dissociation

Abstract: The OH-stretch overtone spectroscopy and dynamics of the hydroxymethyl radical, CH(2)OH, are reported in the region of the second and third overtones, which is above the thermochemical threshold to dissociation to H+CH(2)O (D(0)=9600 cm(-1)). The second overtone spectrum at 10 484 cm(-1) is obtained by double resonance IR-UV resonance enhanced multiphoton ionization (REMPI) spectroscopy via the 3p(z) electronic state. It is rotationally resolved with a linewidth of 0.4 cm(-1) and displays properties of local-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 39 publications
(108 reference statements)
4
25
0
Order By: Relevance
“…Recently, Dames and Golden 49 computed the barrier of 40.0 kcal/mol at the RCCSD(T)/CBS level. In 2006, Wei et al 73 published their spectroscopic experimental result for CH 2 OH → CH 2 O + H. The decomposition barrier they obtained is 43.5 kcal/mol, which is greater than our CCSD(T) value by 4.0 kcal/mol, although their heat of reaction, 27.5 kcal/mol, is almost the same as ours predicted at the CCSD(T) level. It should be mentioned that earlier kinetic measurements 41 gave much smaller barriers, below 30 kcal/mol, for the decomposition process attributable in part to the pressure effect.…”
Section: ■ Results and Discussionsupporting
confidence: 62%
“…Recently, Dames and Golden 49 computed the barrier of 40.0 kcal/mol at the RCCSD(T)/CBS level. In 2006, Wei et al 73 published their spectroscopic experimental result for CH 2 OH → CH 2 O + H. The decomposition barrier they obtained is 43.5 kcal/mol, which is greater than our CCSD(T) value by 4.0 kcal/mol, although their heat of reaction, 27.5 kcal/mol, is almost the same as ours predicted at the CCSD(T) level. It should be mentioned that earlier kinetic measurements 41 gave much smaller barriers, below 30 kcal/mol, for the decomposition process attributable in part to the pressure effect.…”
Section: ■ Results and Discussionsupporting
confidence: 62%
“…The production of H atoms upon excitation near the estimated 4ν 1 ← 0 transition was observed with the action spectrum showing a partially resolved rotational structure. In similar studies of CD 2 OH, 13 only H fragments were observed, indicating that isomerization to CHD 2 O was at best a minor channel, despite the fact that the available calculations 3,15 all placed the barrier for isomerization to methoxy lower than the barrier for OH bond breaking. As described previously, 10, 15 the minimum energy structure of CH 2 OH is non-planar and non-symmetric (C 1 ) with unequal CH bond lengths.…”
Section: Introductionmentioning
confidence: 95%
“…Gas-phase spectroscopic studies of vibrational levels such as the symmetric and antisymmetric CH stretch fundamental vibrations of CH 2 OH, as well as excitation of 1-4 quanta of the OH stretch (ν 1 mode) were reported previously. [11][12][13] Perhaps the most intriguing result of the previous studies was the observation of overtone-induced vibrational predissociation of CH 2 OH upon excitation of the 4ν 1 vibrational level. 13 In these studies, the excited OH bond coincided with the bond that was broken.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental OH stretch was measured at 3650 cm À1 in Ar-matrix and at 3637 cm À1 in N 2 -matrix. The overtone spectra were also measured up to v OH ¼ 4 [58] giving! ¼ 3857.7(29) cm À1 and!x ¼ 91.4(10) cm À1 , leading to is (OH) ¼ 3674.9 cm À1 .…”
Section: Pentaatomic Speciesmentioning
confidence: 99%